Professionals' and Intercultural Mediators' Perspectives on Communication With Ukrainian Refugees in the Czech Healthcare System - Jolana Kopsa Těšinová; Karolína Dobiášová; Marie Jelínková; Elena Tulupova; Michal Koščík (Wiley, 2024)
ABSTRACT Introduction A growing body of research is examining how healthcare systems are responding to the increasing numbers of migrants and the resulting superdiversity of patients. The aim of this article is to identify and explain communication barriers in the provision of healthcare to Ukrainian war refugees in the Czech Republic from the perspectives of healthcare professionals and intercultural mediators. Methods The exploratory case study is based on a qualitative analysis of semi‐structured interviews with frontline health professionals: 20 with doctors and 10 with nurses. The second source of data is two focus groups aimed at capturing communication problems from the perspective of intercultural mediators who accompany refugees to health facilities. The interview transcripts and FGs were analysed using six‐stage thematic coding. Results The survey identified five main themes related to barriers to communication: (1) language barriers and interpreting, (2) cultural barriers, (3) differing expectations of health and the healthcare systems in the Czech Republic and Ukraine, (4) prejudices and negative attitudes and unethical behaviour towards refugees and migrants and (5) lack of awareness of patient rights. Conclusions The arrival of large numbers of migrants has highlighted deficiencies in the system that may affect other vulnerable groups and the general population. These include the lack of general communication skills and legal awareness among many health professionals, which are barriers to the development of patient‐centred care. The involvement of intercultural mediators fundamentally improves communication between health professionals and (not only) migrant patients. Nevertheless, it is necessary to legally anchor and define the position of intercultural mediators within the healthcare system. Patient or Public Contribution Collaboration with intercultural mediators who interpreted the extensive experiences of Ukrainian refugee patients and also have personal experience as migrant or migrant‐origin patients contributed to shaping research questions, facilitating study participation and enriching evidence interpretation. Researchers with multicultural backgrounds and experience with working with people from refugee backgrounds were involved in the study design and analysis.